Brands and branding - Clifton, Rita.; Ahmad, Sameena (London : Profile Books, 2009)
This collection examines the history and definition of brands, their financial and social importance, current best practices in branding, future opportunities offered by globalization, and the potential of Asian brands. Topics of the 15 articles include the visual and verbal identity of well-known companies, the laws governing brand protection, corporate social responsibility, and branding places and nations.
Introduction / Rita Clifton -- What is a brand? / Tom Blackett -- The financial value of brands / Jan Lindemann -- The social value of brands / Giles Gibbons -- What makes brands great / Jez Frampton -- Brand strategy / Iain Ellwood -- Brand experience / Shaun Smith -- Visual and verbal identity / Tony Allen and John Simmons -- Brand communications / Paul Feldwick -- The public relations perspective on branding / Deborah Bowker -- Brand protection / Allan Poulter -- Globalisation and brands / Sameena Ahmad -- Branding in asia / Jonathan Chajet -- From elephant to tiger : brands and branding in india / Max Raison -- Branding places and nations / Simon Anholt -- Brand 2.0 : brands in a digital world / Andy Hobsbawm -- An alternative perspective on brands : markets and morals / Deborah Doane -- The future of brands / Rita Clifton.
Keywords: Brand name products; Branding (Marketing); kulttuurienvälisyys; kulttuurienvälinen viestintä; brändit; merkkitavarat; kulttuurierot; mielikuvat; strategiat; tuotteet; markkinointi; tavaramerkit; viestintä